The Review of the Mediating Role of Organizational Agility in The Impact of Entrepreneurial Orientation on Corporate Performance - Zhen, Liu; Ali, Dhakir Abbas (Journal of Ecohumanism, 2024)
This article explores the role of organizational agility as a mediator between entrepreneurial orientation and business success. The research delves into the definitions and significance of entrepreneurial orientation, organizational agility, and corporate performance, providing a thorough literature review to understand the interactions among these components. Employing a comprehensive review of existing literature and empirical investigations, the study presents evidence that organizational agility significantly impacts both entrepreneurial orientation and company success. Specifically, it mediates the positive effects of entrepreneurship on performance. The findings emphasize the importance of understanding these elements to grasp the intricate relationship between entrepreneurial orientation and business success. The research offers valuable insights for firms aiming to enhance their management practices and strategic decision-making, particularly in adapting to a rapidly changing business environment. It establishes a robust theoretical foundation for understanding the interplay between entrepreneurial orientation, organizational agility, and corporate performance, offering practical guidance for businesses seeking to refine their strategic management approaches. Future research should continue to explore the effects of organizational agility on entrepreneurial orientation and corporate success, with a particular focus on contextual factors that might influence this mediation.